Governing Cities in a Global Era - Hambleton, R. author. aut Link
XXI, 267 p.
Keywords: This book is about the role that ideas, institutions, and actors play in structuring how we govern cities and, more specifically, what projects or paths are taken. Global changes require that we rethink governance and urban policy, and that we do so through the dual lens of theory and practice.